Novel adomavirus associated with proliferative skin lesions affecting the dermal denticles of a sand tiger shark (Carcharias taurus) - Powell, Ashley L.; Camus, Alvin C.; Leary, John H.; Miller, Sarah N.; Bell, Cynthia M.; Ng, Terry Fei Fan (Frontiers in Veterinary Science, 2024)
A captive sand tiger shark (Carcharias taurus) presented with progressive, hard, raised, miliary skin lesions localized to the lateral trunk and peduncle. Histopathologic evaluation of biopsy samples revealed dysplastic proliferation of odontogenic epithelium with the production of collagenous material. Inclusion bodies and viral particles were not observed with light or transmission electron microscopy, respectively. However, using next generation sequencing with Illumina MiSeq and PCR followed by Sanger sequencing, the complete genome of a novel adomavirus, tentatively named sand tiger shark adomavirus (STAdoV), was obtained from the affected tissue. The genome was circular and 18.5 kilobases with bidirectionally transcribed genes, namely EO1, EO2 & 4, EO3, LO4, LO5, LO6, LO7, LO8, and SET. In situ hybridization using RNAscope® technology and a STAdoV specific probe localized viral DNA to the nuclei of proliferating epithelial cells. Adomaviruses are an emerging viral group with structural and replicative genes sharing a complex evolutionary history with adenoviruses and small circular DNA tumor viruses including papillomaviruses and polyomaviruses. Adomaviruses are described in a number of fish species in association with both necrotizing and proliferative diseases. BLAST analysis of the viral genome revealed greatest nucleotide identity (71.29%) to guitarfish adomavirus (GAdoV), another elasmobranch virus associated with proliferative (epidermal) skin lesions. Lesions in the index animal persisted for approximately 1 year during which time four conspecifics developed similar proliferations. Ultimately, lesions in all sharks regressed spontaneously without recurrence for 2 years.